Ecohealth approach to urban waste management: Exposure to environmental pollutants and health risks in Yamoussoukro, Côte d’Ivoire - Kouamé, P.K.; Dongo, K.; Hung Nguyen-Viet; Zurbrugg, C.; Lathi, C.; Hattendorf, J.; Utzinger, J.; Biemi, J.; Bonfoh, Bassirou (MDPI, 2014)
Poor waste management is a key driver of ill-health in urban settlements of developing countries. The current study aimed at assessing environmental and human health risks related to urban waste management in Yamoussoukro, the political capital of Côte d’Ivoire. We undertook trans-disciplinary research within an Ecohealth approach, comprised of a participatory workshop with stakeholders and mapping of exposure patterns. A total of 492 randomly selected households participated in a cross-sectional survey. Waste deposit sites were characterised and 108 wastewater samples were subjected to laboratory examinations. The physico-chemical parameters of the surface water (temperature, pH, conductivity, potential oxidise reduction, BOD5, COD, dissolved oxygen, nitrates, ammonia and total Kendal nitrogen) did not comply with World Health Organization standards of surface water quality. Questionnaire results showed that malaria was the most commonly reported disease. Diarrhoea and malaria were associated with poor sanitation. Households having dry latrines had a higher risk of diarrhoea (odds ratio (OR) = 1.8, 95% confidence interval (CI) 1.2–2.7) compared to latrines with septic tanks and also a higher risk for malaria (OR = 1.9, 95% (CI) 1.1–3.3). Our research showed that combining health and environmental assessments enables a deeper understanding of environmental threats and disease burdens linked to poor waste management. Further study should investigate the sanitation strategy aspects that could reduce the environmental and health risks in the study area.